2014
DOI: 10.1111/cas.12369
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus and p53 mutations in head and neck squamous cell carcinoma among Japanese population

Abstract: We aimed to reveal the prevalence and pattern of human papillomavirus (HPV) infection and p53 mutations among Japanese head and neck squamous cell carcinoma (HNSCC) patients in relation to clinicopathological parameters. Human papillomavirus DNA and p53 mutations were examined in 493 HNSCCs and its subset of 283 HNSCCs. Oropharyngeal carcinoma was more frequently HPV-positive than non-oropharyngeal carcinoma (34.4% vs 3.6%, P < 0.001), and HPV16 accounted for 91.1% of HPV-positive tumors. In oropharyngeal carc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
86
2
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(103 citation statements)
references
References 35 publications
6
86
2
2
Order By: Relevance
“…Thus, in this study, experienced pathologists in our hospital defined patients with the immune-positive cell ratio of 25% or more in tumor cells as having p16 positivity, according to previous report (15). In this study, the p16-positive rate was 43.75%, which is in line with previous data (9,20,(22)(23)(24)(25).…”
Section: Discussionsupporting
confidence: 86%
“…Thus, in this study, experienced pathologists in our hospital defined patients with the immune-positive cell ratio of 25% or more in tumor cells as having p16 positivity, according to previous report (15). In this study, the p16-positive rate was 43.75%, which is in line with previous data (9,20,(22)(23)(24)(25).…”
Section: Discussionsupporting
confidence: 86%
“…In contrast with the West, there has been relatively little interest from Asian nations on this newly recognized disease. In Asia, the reported prevalence of HPV in oropharyngeal cancer ranges from 0% to 34.4% (9)(10)(11)(12). Similar to those reported from Europe and North America, a recent multicenter study from Korea showed an increase in the proportion of tonsillar SCC due to HPV from 5.9% in 1991 to 31.6% in 2009 (13,14).…”
Section: Introductionmentioning
confidence: 56%
“…Inactivating p53 mutations are rarely seen in HPV-positive tumours (7.1%) compared with HPV-negative tumours (48.3%), with inactivation of p53 achieved by the HPV E6 protein [27]. Degradation of the p53 protein results due to the binding of E6 to E3 ubiquitin ligases leading to cell cycle deregulation, due to loss of p21 function and loss of p53-mediated apoptosis [27,28]. Additionally, E6 interacts with pro-apoptotic proteins Bak and procaspase 8 to prevent apoptosis and activates telomerase associated with cell immortalization [29,30] (Fig.…”
Section: Molecular Pathogenesis Of Hpv-associated Oral Cancersmentioning
confidence: 99%
“…The oncogenic E6 and E7 of HR-HPV16/18 inactivate critical tumour suppressor genes, p53 and pRb. Inactivating p53 mutations are rarely seen in HPV-positive tumours (7.1%) compared with HPV-negative tumours (48.3%), with inactivation of p53 achieved by the HPV E6 protein [27]. Degradation of the p53 protein results due to the binding of E6 to E3 ubiquitin ligases leading to cell cycle deregulation, due to loss of p21 function and loss of p53-mediated apoptosis [27,28].…”
Section: Molecular Pathogenesis Of Hpv-associated Oral Cancersmentioning
confidence: 99%